Living Conditions of Adolescents Who Have Attempted Suicide in Mexico - Valdez-Santiago, Rosario (Int J Environ Res Public Health, 2020)
Suicidal behavior represents a complex public health problem, with a rising number of suicide attempts registered among Mexican adolescents. We undertook a qualitative study in order to understand the living conditions of adolescents who had attempted to take their lives in five Mexican states. We interviewed 37 adolescents who had engaged in suicide attempts in the year prior to our study. To code and analyze the information, we defined the following three categories of living conditions as social determinants of health for adolescents: poverty and vulnerability, education, and health care. To this end, we followed the methodology proposed by Taylor and Bogdan, and used Atlas.ti 7.5.18 software for analyses. Among our findings, we noted that poverty, manifested primarily as material deprivation, rendered the daily lives of our interviewees precarious, compromising even their basic needs. All the young people analyzed had either received medical, psychological, and/or psychiatric care as outpatients or had been hospitalized. School played a positive role in referring adolescents with suicidal behavior to health services; however, it also represented a high-risk environment. Our findings highlight the urgent need to implement a national intersectoral strategy as part of comprehensive public policy aimed at improving the health of adolescents in Mexico.